Metode Permainan Pantomime dalam Penguasaan Kosakata Verba - Balqis Zahrani Fitri; Syukur Saud; Syarifah Fatimah (Universitas Negeri Makassar, 2024)
Abstract. This research is a Quasi-Experimental research which the purpose is to describe the effectiveness of Pantomime game method on verb mastery of students of class X at SMA Negeri 10 Makassar. The population of this research is students of class X at SMAN 10 Makassar who study German (X IPA 6, X IPA 7, X IPA 8, and X IPS 3). The sample was selected using random sampling technique with total of 30 samples for each class, which is the experimental class (X IPS 3) and control class (X IPA 8). Verb mastery of the students are seen from the pre-test and post-test execution. The result of both tests for the experimental class has the average score of 56,3 for pre-test and 79,2 for post-test. The research data were processed using the paired T-test. The result of the t-test calculation showed that the score of Sig. (2-tailed) of pre-test and post-test of the experimental class is 0.000, which means the hypothesis is accepted and could be concluded that the application of Pantomime game method is effective on verb masteryKeywords: Effectiveness, Pantomime, Verb